Firm heterogeneity, informal wage and good governance - Saibal Kar; Sugata Marjit (Institute for the Study of Labor (IZA), 2011)
We provide an analysis of enforcement policies applicable to formal sector in dual labor markets. We use a framework with heterogeneous firms, endogenous determination of informal wage and politically dictated enforcement strategies. Firms which operate both in the formal and informal sectors do very little to increase employment when faced with the opportunity of hiring workers in the informal labor market. Thus enforcement of labor laws and other regulations should not have aggregate employment effects, particularly when workers are productively homogeneous. For firms operating exclusively in the informal sector, the outcome is different. Such features determine the stringency of enforcement in a market characterized by firms with varying levels of productivity. For example, in case of firms with relatively high levels of productivity, enforcement has to be stricter than in the case with relatively low productivity firms. Taxing the more productive seems to be the optimal strategy.
urn:nbn:de:101:1-201110102360
Keywords: J21; J31; J50; 330; heterogeneous firms; informal labor; wage; labor regulations; enforcement; Informeller Sektor; Lohn; Arbeitsrecht; Rechtsdurchsetzung; Unternehmen; Produktivität; Dualer Arbeitsmarkt; Theorie